Dyslipidemia in Patients with a Cardiovascular Risk and Disease at the University Teaching Hospital of Yaoundé, Cameroon. (9th January 2017) - Ama Moor, Vicky Jocelyne; Ndongo Amougou, Sylvie; Ombotto, Sebastien; Ntone, Felicien; Wouamba, Doriane Edna; Ngo Nonga, Bernadette
Abstract : Objective . To determine the frequency of lipid abnormalities in patients with a cardiovascular risk and disease at the University Teaching Hospital (UTH) of Yaoundé. Materials and Methods . We conducted a cross-sectional study from 1 March to 31 May 2015 at the UTH of Yaoundé. We included all patients seen in the outpatient department with a diagnosis of a cardiovascular disease or a risk factor for cardiovascular disease. Patients who accepted to participate in the study were asked to answer a questionnaire; after that a blood sample was taken for lipid profile. An informed consent was signed by all the participants and the study has received approval from the national ethic committee. Results . We recruited 264 patients of which 119 were men and 145 were women with a sex ratio of 0.82. Mean age was 61.36 years. The frequency of lipid profiles abnormalities was as follows: low HDL cholesterol (44.3%), hypertriglyceridemia (18.9%), high LDL cholesterol (3.8%), and high total cholesterol 3.4%). Hypertriglyceridemia was strongly associated with type 2 diabetes mellitus. Conclusion . Low levels of HDL cholesterol and hypertriglyceridemia are more prevalent in our study population. More studies are needed to confirm this finding in our environment.